The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1136/heartjnl-2015-308650
|View full text |Cite
|
Sign up to set email alerts
|

The incidence of chromosome abnormalities in neonates with structural heart disease

Abstract: Chromosome abnormalities, including syndromes, are prevalent in newborns with congenital heart disease. Further research is needed to evaluate the utility of cytogenetic screening in all children with congenital heart disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
12
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 19 publications
1
12
2
Order By: Relevance
“…[22][23][24] The proportion of CNVs appeared slightly lower in postnatal cohorts that reported CNVs in 5-8% of neonates with CHDs. 25,26 One recent fetal cohort reported a prevalence of 16% pathogenic CNVs. 27 This proportion, however, reflects a selected population, as they only included those referred for invasive genetic testing.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[22][23][24] The proportion of CNVs appeared slightly lower in postnatal cohorts that reported CNVs in 5-8% of neonates with CHDs. 25,26 One recent fetal cohort reported a prevalence of 16% pathogenic CNVs. 27 This proportion, however, reflects a selected population, as they only included those referred for invasive genetic testing.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of sequence variants appeared also higher in fetuses (6.6%) than neonates, as one postnatal cohort study reported genetic syndromes in 5.1% of neonates with normal chromosomes. 26 This risk is probably higher in fetal cohorts compared to cohorts that focus exclusively on postnatal cases, as cases with TOP, intra uterine fetal demise or early neonatal death are often not included in postnatal cohorts. It is therefore important that our data are evaluated from a prenatal perspective to enable prenatal counseling at midgestation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As recruitment was center-specific, it is possible that differences in recruitment might have introduced some selection bias. For instances, the proportion of cases in the PCGC cohort with a genetic diagnosis (11%) is low compared to population-based estimates (~20%) [ 19 ]. This likely reflects the PCGC recruitment priorities (e.g., nonsyndromic over syndromic) and it is possible that some centers may have recruited a lower proportion of syndromic cases than other centers.…”
Section: Discussionmentioning
confidence: 99%
“…However, with the emergence of genetic technologies such as chromosomal microarray, targeted gene panels and whole exome/genome sequencing, establishing a molecular diagnosis for patients with CHD, are fast becoming a reality, even in those with sporadic forms of disease. 9,10 An important question asked by many parents at the time of diagnosis is "how and why did this happen?". 11 A lack of understanding leaves many parents with feelings of "transmission guilt," which may progress to feelings of distress and shame over their perceived wrongdoing in passing on the disease, and ultimately manifesting into depression, anxiety, and stress.…”
mentioning
confidence: 99%